Tinjauan Hukum Berdasarkan Statuta Roma terhadap Perlindungan Perekrutan Tentara Anak di Bawah Umur dalam Konflik Bersenjata Internasional - Aristya Nadya Azhari; Faiq Muhammad Zufar; Chornilia Shilvi; Louisa Aulia; Yulius Prasetyo Herlambang (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
International humanitarian law (HHI) aims to protect individuals who are not involved in armed conflict, including children who are often victims or even perpetrators of warfare. The phenomenon of recruitment of child soldiers, although prohibited in various international legal instruments, but still takes place in a number of countries in conflict. This research discusses the legal implications for parties that violate the provisions regarding the recruitment of child soldiers, focusing on the provisions in the Rome Statute that classify the recruitment of child soldiers as a war crime. In addition, it analyses the underlying causes of the armed conflict in Sudan and how international accountability mechanisms can be optimised to prosecute perpetrators of crimes against children. In addition, it identifies opportunities and constraints in realising justice for child victims of armed conflict, as well as the importance of international cooperation in providing protection and rehabilitation for them. It is hoped that the findings will provide further insight into the challenges and efforts needed to protect children's rights in the midst of war and the importance of international law enforcement to prevent the exploitation of children in armed conflict.